PENINGKATAN KOMPETENSI GURU DALAM PENGGUNAAN QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN IPA INTERAKTIF SD NEGERI 139/III LEMPUR MUDIK - Shobrina Fitri; Muhammad Ali Imron; Egi Agustandi; Ferinaldi; Diva Apri Mulya; Yudhistira Ahmad; Wira Hadi Kusuma (Hira Institute, 2024)
The development of information and communication technology (ICT) provides a great opportunity to create interactive and effective learning. This workshop aims to improve the competence of teachers at SDN 139/III Lempur Mudik in using the Quizizz application as an interactive science learning media. The activity involved 10 teachers, which was carried out through theory, practice, and evaluation sessions. The evaluation results showed that 80% of participants understood the use of Quizizz well based on the pre-test and post-test. Teachers were also able to create interactive quizzes with good quality, and the participation rate reached 90%. Obstacles such as limited devices and adaptation to technology were successfully overcome through mentoring solutions and the provision of additional devices. This workshop made a positive contribution to learning innovation in elementary schools, with the hope of continued mentoring for the sustainability of the program. Keywords: learning technology, Quizizz, teacher competence, interactive science.